If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2x = 27 Reorder the terms: 2x + y = 27 Solving 2x + y = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 2x + y + -1y = 27 + -1y Combine like terms: y + -1y = 0 2x + 0 = 27 + -1y 2x = 27 + -1y Divide each side by '2'. x = 13.5 + -0.5y Simplifying x = 13.5 + -0.5y
| S-11=(-34) | | (z^2-2iz)*(z^2+25)=0 | | 3x+3=-25 | | -11=s+5 | | (-11)=13+x | | 15/25=y/30 | | (-15)+g=(-5) | | (2c+9)(c+5)= | | f(x)=6x^3+8x^2+3 | | 6(1-2x)-x=-46 | | B-17=-38 | | 6+2x=5-(7x) | | J+13=37 | | a^2+4ab+4b^2=0 | | M+(-10)=(-2) | | -3a+8=2 | | 4x-3y=52 | | (-17)=(-9)+q | | f(x)=a^3-3a^2-9 | | 2.25=3/4(b-5) | | 17+n=4 | | 6x-x^2+16= | | (-22)+j=(-24) | | 72.8=7(m+3.1) | | 4x+23=75 | | (2c+9)x(c+5)= | | 3[m-1.2]=9 | | h-8+2(h-8)=72 | | 47=19-4x | | 39+x=30+2x | | R-20+4=18 | | 1521=39p+390 |